ANALISIS RASIO KEUANGAN PADA KOPERASI MADU KELULUT “KUKAR IDAMAN LESTARI” DI KELURAHAN MANGKURAWANG TENGGARONG - Palinggi, Yonathan; Erwinsyah, Erwinsyah; Akbar, Ali; S, Syahruddin; Ilham, Ilham; Juanda, Rendy; Hermanto, M.; Amir, Kartika Sari (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2024)
This research was conducted to determine and examine the financial performance of a Cooperative. This research was conducted at the Kelulut Honey Cooperative